2013
DOI: 10.1103/physrevlett.111.197204
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer Magnetoresistance due to Chiral Soliton Lattice Formation in Hexagonal Chiral MagnetCrNb3S6

Abstract: We investigate the interlayer magnetoresistance (MR) along the chiral crystallographic axis in the hexagonal chiral magnet CrNb 3 S 6 . In a region below the incommensurate-commensurate phase transition between the chiral soliton lattice and the forced ferromagnetic state, a negative MR is obtained in a wide range of temperature, while a small positive MR is found very close to the Curie temperature. Normalized data of the negative MR almost falls into a single curve and is well fitted by a theoretical equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
103
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(116 citation statements)
references
References 24 publications
7
103
2
2
Order By: Relevance
“…Recently, Togawa et al directly observed the CSL structure in CrNb 3 S 6 using Lorentz transmission electron microscopy, and found that the chiral magnetic structures are very stable against crystal defects [11]. With this result, CrNb 3 S 6 is recognized as one * Electronic address: shinozaki@vortex.c.u-tokyo.ac.jp of the candidates of new magnetic devices [12]. In addition to CrNb 3 S 6 , YbNi 3 Al 9 was also discovered as another mono-axial chiral helimagnet with heavy-electron behavior, where the periodicity of the helix is comparable to lattice constant [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Togawa et al directly observed the CSL structure in CrNb 3 S 6 using Lorentz transmission electron microscopy, and found that the chiral magnetic structures are very stable against crystal defects [11]. With this result, CrNb 3 S 6 is recognized as one * Electronic address: shinozaki@vortex.c.u-tokyo.ac.jp of the candidates of new magnetic devices [12]. In addition to CrNb 3 S 6 , YbNi 3 Al 9 was also discovered as another mono-axial chiral helimagnet with heavy-electron behavior, where the periodicity of the helix is comparable to lattice constant [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The first three terms give the energy of the conical helix with wave vector q 0 , while the term proportional to β x is the difference between the conical helicoid, (12), and the conical helix. We write the energy in this way for later convenience.…”
Section: Comparison With Simplifying Approximationsmentioning
confidence: 99%
“…As * laliena@unizar.es † javier.campo@csic.es the field increases, the regions where the spins rotate slowly become very wide and the regions where the spins rotate rapidly become very narrow, and a chiral soliton lattice (CSL) is formed [1,[5][6][7]. This CSL, which is realized in CrNb 3 S 6 [8], supports dynamic modes like coherent sliding [9] and gives rise to exciting phenomena such as spin motive forces [10] and tunable magnetoresistance [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Межслойное магнитосопротивле-ние вдоль оси c дало значение температуры Кюри мо-нокристаллов 132 K [4]. Исследования спин-релаксации µ-мюонов в монокристаллах CrNb 3 S 6 дали оценку T c около 127 K [5].…”
Section: еб борисенко ва березин нн колесников вк гартманunclassified
“…Для исследования структуры выращенных кристаллов использовалась дифрактометрическая съем-ка монокристаллов. Различные магнитные методы, при-меняемые ранее для определения температуры Кюри соединения CrNb 3 S 6 [1,[3][4][5] давали отличающиеся друг от друга значения температур ферромагнитного перехо-да. В связи с этим был разработан и применен новый метод оценки температуры ферромагнитного перехода, основанный на температурной и полевой зависимо-стях высокочастотного (ВЧ) поглощения в кристаллах CrNb 3 S 6 в переменном магнитном поле.…”
Section: Introductionunclassified